Factors influencing the achievement of core acute flaccid paralysis indicators in the Western North Region, Ghana, 2022 - Obed Bangdome Ofori; Joseph Asamoah Frimpong; Isaac Baffoe-Nyarko; Azumah Abdul-Tawab; Horlali Yao Gudjinu; Eunice Baiden Laryea; Marion Okoh-Owusu; Ernest Kenu; Dennis Odai Laryea; Franklin Asiedu-Bekoe (Journal of Interventional Epidemiology and Public Health, 2025)
Background: In response to polio outbreaks, Ghana enhanced its Acute Flaccid Paralysis (AFP) surveillance system, revising the target for the Non-polio AFP (NP-AFP) rate for children under 15 years from at least 2 to 3 cases per 100,000 population. However, some districts in the Western North Region (WNR) continue to fall short of achieving both the NP-AFP rate and stool adequacy targets. This study examined factors influencing the achievement of core AFP indicators in the WNR.